Teacher burnout and turnover intention in higher education: The mediating role of job satisfaction and the moderating role of proactive personality - Zhang, Qun; Li, Xianyin; Gamble, Jeffrey Hugh (Frontiers in Psychology, 2022)
Teacher burnout and frequent turnover negatively affect stability and productivity in the context of higher education. Despite the fact that the relationship between burnout and turnover intention has been thoroughly studied, the role of other factors in this relationship should be evaluated in order to better clarify underlying mechanisms, particularly in the context of higher education. In this study, we first aim to bridge a research gap by utilizing job satisfaction as a mediating variable for the relationship between burnout and turnover intention. Moreover, we uniquely evaluate the role of proactive personality as a moderating variable, first in terms of the relationship between burnout and job satisfaction, and then for the relationship between job satisfaction and turnover intention. Based on 296 valid questionnaires collected from university faculty members in China, proposed hypotheses were evaluated empirically. The results demonstrate that, as expected, burnout has a significant and positive impact on turnover intention, and job satisfaction has significantly negative impact on turnover intention, with job satisfaction partially mediating the relationship between burnout and turnover intention. Moreover, proactive personality moderated the relationship between job satisfaction and turnover intention, with this relationship being stronger for individuals with high proactive personality as compared to low proactive personality. These findings provide a better understanding of the relationship between burnout and turnover intention of university instructors. Theoretical and practical implications, limitations, and recommendations for further research are provided.